Risiko Gangguan Seksual Di Dalam Rumah Kepada Remaja - Norsaleha Mohd. Salleh; Kamal Azmi Abd. Rahman; Noor Hafizah Mohd. Haridi; Norbahiah Misran; Zetty Nurzuliana Rashed; Nabilah Huda Zaim (FPPI, KUIS, 2024)
Sexual harassment is a sexually oriented act committed against another person either verbally, non-verbally, physically, or emotionally. Sexual harassment can occur to female teenagers whether they are inside or outside home. This quantitative study used questionnaires that were analysed using SPSS 2.0. The objective of the study is to explore the extent of domestic sexual harassment risk on female teenagers while they are at home. A total of 84 girls from the age of nine to fifteen in Selangor participated in this study where they have received consent from their parents and guardians to participate in this study. This study found that 7.14% of the participants admitted that they like to wear sexy clothes at home and had watched pornographic videos with close family members such as father, brother, uncle, and grandfather. The findings revealed that they had experienced sexual harassment by their family members if they do not maintain the Islamic manners in addition to being excessively exposed to the unlimited information technology facility. The findings also showed that there are unsafe elements towards female teenagers at home if the family well-being mechanism is not properly and well maintained. The implications of this study suggested a development of a mobile application to identify the initial signs of sexual harassment towards female teenagers.